Proceedings IEEE 56th Vehicular Technology Conference
DOI: 10.1109/vetecf.2002.1040698
|View full text |Cite
|
Sign up to set email alerts
|

Wireless LAN performance under varied stress conditions in vehicular traffic scenarios

Abstract: Mobile ad-hoc networking with wireless LAN infrastructure can be employed to build inter-vehicle communication based applications. The associated high velocities and hostile driving environments pose a challenge to the performance of a wireless LAN. This paper assesses the performance of a wireless Local Area Network in different vehicular traffic and mobility scenarios. The network throughput and the quality of the wireless communication channel, measured on IEEE 802.11b compliant equipment, are observed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 4 publications
0
65
0
1
Order By: Relevance
“…1. Further, since vehicles exhibit large variability in speed by assuming maximum as well as minimum speeds during mobility, the VANET connectivity can be intermittent, with the mobile communication link quality degrading significantly with inter-vehicular distance [4].…”
Section: Mobility and Application Constraints Of Vanetmentioning
confidence: 99%
See 2 more Smart Citations
“…1. Further, since vehicles exhibit large variability in speed by assuming maximum as well as minimum speeds during mobility, the VANET connectivity can be intermittent, with the mobile communication link quality degrading significantly with inter-vehicular distance [4].…”
Section: Mobility and Application Constraints Of Vanetmentioning
confidence: 99%
“…(3) A group of navigating vehicles within a distance r 0 /2, where r 0 is vehicle transmission range, are geophysically proximate and can maintain full connectivity, and the group communication does not suffer any significant signal degradation. For instance, given that r 0 = 300 m is a typical value [1], it is shown in [4] that signal-tonoise ratio (SNR) for mobile communication between vehicles within a distance of 150 m on a freeway is adequate to provide reliable communication. Based on the above observations, we propose to enable vehicles to form a group during navigation.…”
Section: B Use Of Group Concept To Extend Silent Period In V2i Applimentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Singh (Singh et al 2002) conducted several field tests and concluded that 802.11b performance is "suitable for intervehicle communications." These papers are not in conflict, but rather interpret "suitability" in different ways.…”
Section: Its/doc Group Initial Project Descriptionmentioning
confidence: 99%
“…The probability is referred to as the reception probability. We adopt the empirical results of [5] to determine the reception probability. Specifically, given the relative speed s, the ratio between the 802.11b throughput under s and that under relative speed 0 is obtained from [5].…”
Section: Simulation Of Mobility and Resourcesmentioning
confidence: 99%